Diospyros malabarica Fruit Extract Derived Silver Nanoparticles: A Biocompatible Antibacterial Agent - Polash, Shakil Ahmed; Hamza, Amir; Hossain, Md. Monir; Tushar, Mehedi Hasan; Takikawa, Masato; Shubhra, Razib Datta; Saiara, Noshin; Saha, Tanushree; Takeoka, Shinji; Sarker, Satya Ranjan (Frontiers in Nanotechnology, 2022)
Biogenic silver nanoparticles exhibit excellent antibacterial activity against a broad range of bacteria. Herein, aqueous biogenic silver nanoparticles (Aq@bAgNPs) and ethanolic biogenic silver nanoparticles (Et@bAgNPs) were synthesized using aqueous as well as ethanolic extracts of Diospyros malabarica fruit, respectively. The as-prepared biogenic silver nanoparticles (bAgNPs) were characterized using UV-Vis, FTIR as well as energy dispersive X-ray (EDS) spectroscopy, electron microscopy, dynamic light scattering spectroscopy (DLS), and zetasizer. The zeta potentials of Aq@bAgNPs and Et@bAgNPs were -9.8±2.6, and -12.2±1.9 mV, respectively. The antibacterial activity of bAgNPs was investigated against 7 bacterial strains (i.e., pathogenic and nonpathogenic) and Et@bAgNPs exhibited the highest antibacterial propensity (i.e., 20 nm in diameter) against Bacillus subtillis through disk diffusion assay. The CellToxTM Green assay and trypan blue dye exclusion assay also confirmed the antibacterial propensity of as-prepared bAgNPs. Furthermore, both Aq@bAgNPs and Et@bAgNPs oxidize bacterial membrane fatty acids and generate lipid peroxides which eventually form complexes with thiobarbituric acid (i.e., malondialdehyde-thiobarbituric acid adduct) to bring about bacterial death. Both the nanoparticles demonstrated good hemocompatibility against human as well as rat red blood cells (RBCs). In addition, they exhibited excellent biocompatibility in vivo in terms of rat liver (i.e.., serum ALT, AST and γ-GT) and kidneys (i.e., serum creatinine) function biomarkers.